Paediatric burns patients: Reasons for admission at a tertiary centre. Issue 4 (June 2015) - Marino, M.J.; Kimble, R.M.; Stockton, K.A.
Highlights The reasons for admission to a tertiary burns centre in children with a burns injury was determined. A majority (45%) were admitted for severity, followed by region of body burnt (24%). One third were admitted for reasons other than the biology of the burn itself. It is not just children with severe burns who are admitted. Multiple non-biological factors directly impact inpatient admissions.